2015
DOI: 10.1007/s12253-014-9885-4
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 V617F, MPL, and CALR Mutations in Essential Thrombocythaemia and Major Thrombotic Complications: A Single-Institute Retrospective Analysis

Abstract: Thrombo-haemorrhagic events are the main cause of morbidity and mortality in essential thrombocythemia. The aim of this study was to estimate the incidence of thrombotic events and the impact of the JAK2V617F, MPL (W515L, W515K, W515R, W515A and S505N) and CALR (type-1, type-2) mutations on 101 essential thrombocythaemia patients (72 females and 29 males with a mean age of 61 years) diagnosed in a Southern Hungarian regional academic centre. The incidence of major thrombosis was 13.86 %. Sixty percent of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
2
11
0
2
Order By: Relevance
“…However, the present study results indirectly support the concept that the JAK2V617F mutation contributes to intrinsic changes in both megakaryocyte and platelet biology beyond the increase in cell numbers [35][36][37]. The results of another single center analyses also revealed that the JAK2 V617F (−) cases did not differ significantly from the JAK2 V617F (+) cases in the incidence of thrombosis [38][39][40]. The number of involved patients might be determinative in view of clear evaluation of the predictive value of the JAK2 V617F mutation in thrombosis [41,42].…”
Section: Discussionsupporting
confidence: 75%
“…However, the present study results indirectly support the concept that the JAK2V617F mutation contributes to intrinsic changes in both megakaryocyte and platelet biology beyond the increase in cell numbers [35][36][37]. The results of another single center analyses also revealed that the JAK2 V617F (−) cases did not differ significantly from the JAK2 V617F (+) cases in the incidence of thrombosis [38][39][40]. The number of involved patients might be determinative in view of clear evaluation of the predictive value of the JAK2 V617F mutation in thrombosis [41,42].…”
Section: Discussionsupporting
confidence: 75%
“…However, another study detected both JAK2 V617F and CALR mutations in a small number of patients, as well as both JAK2 V617F and MPL W515L/S mutations. 21 Any correlation among the three mutations in MPN patients remains to be identified.Interestingly, the age of the JAK2 -mutant group was significantly higher than the CALR -mutant group and the JAK2 , CALR non-mutation group in both Han and Uyghur populations. This supports the fact that age, but not nationality, is the key factor associated with JAK2 mutation rate, and is consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Since CALR mutations discovery, several studies have been correlated these mutations with clinical data and patient outcome in MPN [14][15][16][17][18][19][20][21][22][23][24]. Interestingly, it was described the presence of CALR mutation in peripheral granulocytes of two PV patients negative for both JAK2 V617F and JAK2 exon12 mutations [25].…”
Section: Introductionmentioning
confidence: 99%